2011
DOI: 10.1111/j.2042-7158.2011.01355.x
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro and in-vivo transdermal iontophoretic delivery of tramadol, a centrally acting analgesic

Abstract: The present study reveals that anodal iontophoresis provides current-controlled transdermal delivery of tramadol without significant interspecies differences, and enables the delivery of therapeutic amounts of tramadol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…This can be achieved using eutectic mixtures of local anesthetics, controlled heat, magnetophoresis, iontophoresis,[4647] electroporation, or sonophoresis. [48] Using iontophoresis dermal anesthesia with lignocaine can be achieved. [4950] The effect can be enhanced by adding adrenaline.…”
Section: Controlled Release Drug Therapymentioning
confidence: 99%
“…This can be achieved using eutectic mixtures of local anesthetics, controlled heat, magnetophoresis, iontophoresis,[4647] electroporation, or sonophoresis. [48] Using iontophoresis dermal anesthesia with lignocaine can be achieved. [4950] The effect can be enhanced by adding adrenaline.…”
Section: Controlled Release Drug Therapymentioning
confidence: 99%
“…vertical) Franz cells or horizontal cells, which allow membrane permeation to be investigated, e.g. in porcine skin . In vivo evaluation of the pharmacokinetics of topically administered drugs is more complex.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…In recent years, tramadol has been researched for the treatment of domestic feline pain. Tramadol is a synthetic opioid that exerts analgesic effects by binding to µ-opioid receptors as well as inhibiting neuronal reuptake of norepinephrine and serotonin [4]. Previous studies have shown that tramadol can be used alone or in combination with NSAIDs for the treatment of mild to moderate pain in domestic felines [5,6].…”
Section: Introductionmentioning
confidence: 99%